2012
DOI: 10.1021/jf300976y
|View full text |Cite
|
Sign up to set email alerts
|

Content of Antioxidative Caffeoylquinic Acid Derivatives in Field-Grown Ligularia fischeri (Ledeb.) Turcz and Responses to Sunlight

Abstract: Ligularia fischeri (Ledeb.) Turcz, a commercial leafy vegetable, contains caffeoylquinic acid derivatives (CQAs) as major phenolic constituents. The HPLC chromatograms of leaf extracts collected from different areas in Korea showed a significant variation in CQA amount, and two tri-O-caffeoylquinic acids (triCQAs) were purified and structurally identified by NMR and MS from this plant. Radical scavenging activities among CQAs were found to be increased in proportion to the number of caffeoyl groups. Since this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 35 publications
(88 reference statements)
0
22
0
2
Order By: Relevance
“…The amount of 5-CQA, 4-CQA, 3-CQA, and 3,4-di-CQA was 136.72, 2144.44, 16.81, and 421.93 μg/g fresh weight of fresh Gom-chi, respectively. Different constituents of CQAs in fresh Gom-chi were previously identified by other investigators (Shang et al, 2010;Kim et al, 2012). Kim et al (Kim et al, 2012) reported that methanol extract of air dried Gom-chi contained 5-CQA, 3,4-di-CQA, 3,5-di-CQA, and 4,5-di-CQA.…”
Section: Simultaneous Quantification and Identification Of Cqas From mentioning
confidence: 77%
See 2 more Smart Citations
“…The amount of 5-CQA, 4-CQA, 3-CQA, and 3,4-di-CQA was 136.72, 2144.44, 16.81, and 421.93 μg/g fresh weight of fresh Gom-chi, respectively. Different constituents of CQAs in fresh Gom-chi were previously identified by other investigators (Shang et al, 2010;Kim et al, 2012). Kim et al (Kim et al, 2012) reported that methanol extract of air dried Gom-chi contained 5-CQA, 3,4-di-CQA, 3,5-di-CQA, and 4,5-di-CQA.…”
Section: Simultaneous Quantification and Identification Of Cqas From mentioning
confidence: 77%
“…Different constituents of CQAs in fresh Gom-chi were previously identified by other investigators (Shang et al, 2010;Kim et al, 2012). Kim et al (Kim et al, 2012) reported that methanol extract of air dried Gom-chi contained 5-CQA, 3,4-di-CQA, 3,5-di-CQA, and 4,5-di-CQA. Shang et al, (Shang et al, 2010) found that four major components including 5-CQA, 3,4-di-CQA, 3,5-di-CQA, and 4,5-di-CQA were identified from 70% ethanol extract of air-dried Gom-chi.…”
Section: Simultaneous Quantification and Identification Of Cqas From mentioning
confidence: 77%
See 1 more Smart Citation
“…Similarly, the seasonal factors can affect the phenolic composition of plant tissues during the vegetative cycle [8]. Previously, four major caffeoylquinic acid derivatives were higher in sunlight grown areas, whereas the content of these compounds decreased steadily in shade leaves of Ligularia fischeri [12].…”
Section: Discussionmentioning
confidence: 97%
“…The leaves of this plant have been also used for several medicinal purposes, especially in the treatment of jaundice, scarlet fever, rheumatoid arthritis and hepatic function failure [1]. Previous studies reported that L. fischeri leaves contained phenolic constituents of caffeoylquinic acid derivatives [12], norsesquiterpene deriva-Acta Biologica Hungarica 66, 2015 tives [25], terpenoids, spiciformisins a, b, and monocyclosqualene [13]. Ligularia fischeri extracts were used for various biological activities such as a protective effect against hepatotoxic [4], cancer prevention [1], antimutagenic and antigenotoxic activities [7].…”
Section: Introductionmentioning
confidence: 99%